The Influence of Green Marketing on Repurchase Intention and Customer Loylaty Through Customer Satisfaction as a Mediation Variable - SAFITRI, Retno Vivi; NGATNO, Ngatno; FARIDA, Naili (Journal of Tourism Economics and Policy, 2024)
This research aims to determine the direct influence of green marketing on repurchase intention and customer loyalty and how much customer satisfaction is a mediating variable between Green Marketing on Repurchase Intention and Customer Loyalty on Uniqlo products. The research method used uses a quantitative approach with the explanatory research type. The sample used was 270 respondents, and data collection was done using a questionnaire. The dependent variable in this research is Green Marketing (X). In contrast, the independent variables are Repurchase Intention and Customer Loyalty (Y), while the Customer Satisfaction variable is a Mediation variable (Z). Data analysis used in this research uses the Smart Partial Least Square (PLS) method. The study's hypothesis testing yielded significant findings. Firstly, green marketing positively impacts customer satisfaction, loyalty, and repurchase intention for Uniqlo products, supported by prior research. Secondly, customer satisfaction and loyalty are interlinked, as validated by existing literature. Thirdly, the influence of green marketing through customer satisfaction and repurchase intention significantly affects customer loyalty. These findings emphasize the importance of green marketing strategies in enhancing customer relationships and brand loyalty for Uniqlo products.